Analysis of the application of the AHP method in indicators of potential in the implementation of wind farms - Javarini, Natacha Sousa; Gomes, Vanielle Aparecida do Patrocinio; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2021)
When considering the current world energy scenario, a wind source is one of the great promises for the future. Therefore, further studies on wind projects and their particularities are justified, as it is a renewable source and has the least impact on the environment. This study has as its theme about the indicators that influence the installation of a wind farm, through peer comparisons, according to the multicriteria decision-making method. To do this, use the Analytic Hierarchy Process Method to rank the criteria and indicators that influence such implementation. The AHP uses mathematics to process as preferential, or decision-making groups, being the facilitating method in solving problems through an algorithm. The results indicated the indicator that occupied the first place in the ranking of decision making, which was the environmental one, which in turn had composed of criteria with greater weights in the criteria according to the test performed by the matrix of judgments. In particular, the wind criterion, which stands out in the opinion of the researchers, as being the one that exerts the greatest influence when considering wind farm implantation.